HE4, CA125, the Risk of Malignancy Algorithm and the Risk of Malignancy Index and complex pelvic masses ‐ a prospective comparison in the pre‐operative evaluation of pelvic masses in an Australian population. (14th July 2015) - Richards, Anthony; Herbst, Unine; Manalang, Jane; Pather, Selvan; Saidi, Samir; Tejada‐Berges, Trevor; Tan, Kris; Williams, Paul; Carter, Jonathan
<x xml:space="preserve">Abstract</x> Background Human epididymis protein 4 (HE4) has been proposed as a novel biomarker for the diagnosis of epithelial ovarian cancer. Using HE4 and CA125, the risk of malignancy algorithm (ROMA) has been shown to be effective in the stratification of epithelial ovarian cancer risk. Aims To determine the effectiveness of HE4 and ROMA in the diagnosis of malignancy of women presenting with a complex pelvic mass in an Australian population and to compare it with CA125 and the risk of malignancy index (RMI). Materials and Methods Prospective recruitment of women was conducted between October 2012 and March 2014 (n = 50). CA125 and HE4 serum concentrations were collected and stored for subsequent analysis. Sensitivities, specificities, positive predictive values (PPV) and negative predictive values (NPV) were calculated for HE4, CA125, ROMA and the RMI. Receiver operating characteristic (ROC) area under the curves (AUC) were also calculated for comparison. Results There was a higher HE4 level in women with ovarian cancer compared with women with benign pathology (P = 0.008), and this observation was seen in benign versus stage 1 ovarian cancer women (P = 0.025). HE4 had a better specificity than CA125 for the diagnosis of ovarian cancer in all women (P = 0.022), and this effect was also observed in premenopausal women (P = 0.012). Furthermore, the ROC‐AUC for HE4 was superior than CA125 in all women (P = 0.0451). The ROMA algorithm was not inferior to the RMI calculation in this population. Conclusions In an Australian population, HE4 and ROMA are useful in the diagnosis of epithelial ovarian cancer.